The Role Of Self-Efficacy In Technology Readiness Of Women Entrepreneurs In The Fashion Msme Sector - Warda Silvia Devi; Anissa Lestari Kadiyono; Marina Sulastiana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
In this digital age, digital strategy skills are essential for business sustainability. Nevertheless, many micro-enterprises remain behind due to limited technological competence. This study aims to examine the influence of self-efficacy on the technology readiness of working mothers managing micro businesses in the fashion sector in Bandung City. A total of 114 respondents participated in this study through a paper-based survey using convenience sampling. The instruments used were the Self-Efficacy Scale by Venkatesh et al. (2003) and the Technology Readiness Index by Parasuraman (2000). Based on simple regression analysis, the results showed that self-efficacy did not significantly influence overall technology readiness (p = 0.311). However, there was a significant relationship between self-efficacy and the motivator aspect of technology readiness (p = 0.015). These findings suggest that individuals with higher self-efficacy tend to be more motivated to use technology. Furthermore, external factors such as access to digital tools and training also play an important role in preparing someone to use technology effectively.